KERUSAKAN TEGAKAN TINGGAL AKIBAT EKSPLOITASI HUTAN DENGAN SISTEM TRAKTOR DAN HIGHLEAD - Jurnalis Thaib (Jurnal Penelitian Hasil Hutan, 1985)
Tractor and highlead  yarding  systems  are the most  common  logging systems  in the Indonesian  Selective  Cutting  (TPI) of its tropical rain forest  exploitations.   The study of  the logging system  performances  were conducted   to evaluate the extend  of residual stand damages. Studies in 22 forestry concessions  revealed  that  the  TPI concepts  have not been adopted  satisfactorily.   The study also confirmed that the average number  of trees having 35 cm  minimum diameter  are 11.6-70.8   trees per ha of commercial  species and 18. 7-79.4 trees per ha for all species.  With regard to the  TPI, there  were only  52.6 percent of   the forest  concessions  conformed   with  the specified  conditions  where at least 25 potential  trees per ha should remained  in the residual stands.Comparative  study  with  highlead  yarding  system  indicated  that  average number  of  potential   trees in the  residual stands were 5.1-16.6  trees per ha of  commercial  species and only  6.3-21.  7 trees per ha for all species. None of the concessions  with  highlead logging systems have met  the TPI requirements.The residual stand damage when  using highlead yarding  are significantly  higher (P  < .05) in comparison  with  that of the tractors.The  residual  stand  damages  were 68.7 to  71.7 percent  for  highlead  system  while only  3.9-52.2  percent  for  the  tractor.  The study  concluded  that with  respect to damages, tractor yarding  is preferable over highlead.